Review of the New Caledonian species of the genus Pactola Pascoe, 1876 (Coleoptera: Curculionidae: Eugnomini), with description of two new species - Mazur, Miłosz A. (Zootaxa, 2014)
The two species of the genus Pactola Pascoe known from New Caledonia, P. convexa (Montrouzier) and P. setacea (Montrouzier), are redescribed and two new species (P. magna sp. n. and P. proxima sp. n.) are described. Pactola kanalensis (Perroud) is a new junior synonym of P. setacea (Montrouzier). A neotype of Pactola setacea (Montrouzier) and lectotypes of Pactola convexa (Montrouzier) and Pactola kanalensis (Perroud) are designated. Pactola nigra Hudson is considered conspecific with Pactola variabilis Pascoe but formal synonymy requires further study. Colour photographs of the dorsal habitus and line drawings of taxonomically relevant structures of all species are provided, as well as an identification key to all known species of Pactola.